2022
DOI: 10.1136/openhrt-2021-001861
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off of major bleeding versus myocardial infarction on mortality after percutaneous coronary intervention

Abstract: BackgroundThe choice of antithrombotic therapy after percutaneous coronary intervention (PCI) is heavily dependent on the relative trade-off between major bleeding (MB) and myocardial infarction (MI). However, the mortality trade-off was mostly described in Western populations and remained unknown in East Asians.MethodThis was a retrospective cohort study from 14 hospitals under the Hospital Authority of Hong Kong between 2004 and 2017. Participants were patients undergoing first-time PCI and survived for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The CRUSADE score of the bivalirudin group in the BRIGHT study was (19.6 ± 11.9), that of the reduced-dose group was (26.79 ± 11.32), and that of the recommended-dose group was (27.26 ± 11.57), both of which in our study were higher than those in the BRIGHT study (all P < 0.001). Although all bleeding events increased, the incidence of major bleeding decreased.Studies (27)(28)(29) have shown that reducing the incidence of major bleeding in patients undergoing PCI is associated with postoperative adverse events. In our study, the proportion of ACT values ≥ 350 s in the recommended-dose group was signi cantly higher than that in the reduced-dose group (56.7% vs. 48.2%, P = 0.001), and there was a greater tendency for major bleeding (0.5% vs. 0.3%, P = 0.687).…”
Section: Discussionmentioning
confidence: 99%
“…The CRUSADE score of the bivalirudin group in the BRIGHT study was (19.6 ± 11.9), that of the reduced-dose group was (26.79 ± 11.32), and that of the recommended-dose group was (27.26 ± 11.57), both of which in our study were higher than those in the BRIGHT study (all P < 0.001). Although all bleeding events increased, the incidence of major bleeding decreased.Studies (27)(28)(29) have shown that reducing the incidence of major bleeding in patients undergoing PCI is associated with postoperative adverse events. In our study, the proportion of ACT values ≥ 350 s in the recommended-dose group was signi cantly higher than that in the reduced-dose group (56.7% vs. 48.2%, P = 0.001), and there was a greater tendency for major bleeding (0.5% vs. 0.3%, P = 0.687).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported a strong association between major bleeding and mortality 4,7,12,14,15) . Major bleeding such as intracranial hemorrhage or severe blood loss as can occur in gastrointestinal hemorrhage also may directly result in mortality, although such bleeding events would not explain the prolonged mortality risk observed after a major bleeding event.…”
Section: Major Bleeding and Subsequent Mortalitymentioning
confidence: 99%